Logistics Performances of Gulf Cooperation Council’s Countries in Global Supply Chains - Stojanović, Ilija; Puška, Adis (Decision Making: Applications in Management and Engineering, 2021)
Regional integration into the Gulf Cooperation Council has enabled respective countries to effectively participate in global supply chains. To ensure effective integration of this region into global supply chains, logistics operations are a very important determinant. The aim of this study was to assess logistical performances of GCC countries, and to identify which country has the best conditions for establishing a regional logistic center. For this study, we used relevant data from Logistics Performance Index (LPI) developed by the World Bank. The research was conducted using a hybrid multicriteria approach based on the CRITIC and MABAC methods. The findings of this study indicate that the United Arab Emirates has the best conditions for establishing a regional logistics center. This study also releveled the areas of logistics in which other GCC countries should make an improvement to improve their logistical performance.